Edleise MENDES (Ed.). Diálogos Interculturais: Ensino e Formação em Português Língua Estrangeira. Campinas, SP: Pontes Editores. 2011. 310 pp. ISBN: 978-85-7113-362-4 [Recensão] - Mendes, Sónia (Linguarum Arena, 2018)
.